Electric vehicle drivers' search for charging convenience: The role of pricing and paths to effective segmentation - Thibault Buraglio; Malte Bleeker; Sven Reinecke (Marketing Review St.Gallen, 2024)
In the current market landscape, charging convenience is critical for EV drivers. They pay little attention to price and show low loyalty to any provider. Additionally, there are distinct segments of EV drivers. For example, one segment relies on public charging for long trips only, while another segment depends on it exclusively for everyday use. Providers need to consider such diverse needs and offer tailored services to effectively capture market share in today's and tomorrow's market.
Keywords: 650